Access to Medical Residency: A Qualitative Study of Medical Graduates' Experiences in Georgia - Mariam Kirvalidze; Mariam Kasrashvili; Aleksandre Tskitishvili; Giorgi Aladashvili; Nikoloz Chelidze; Nikoloz Tvildiani; Karsten Lunze; Ilia Nadareishvili (Journal of Medical Education and Curricular Development)
Objectives Strategic planning for the health workforce–particularly in emerging middle-income countries like Georgia–is essential for maintaining an effective healthcare system. Medical residency training is crucial for developing a well-rounded healthcare workforce equipped with the competencies needed to deliver high-quality care and maintain a balance of specialties. Understanding the enrollment process and experiences of medical graduates in residency programs can help identify areas for improvement. These insights can inform interventions to develop a physician workforce that aligns with population needs and remains responsive to the evolving healthcare system. We aimed to explore the experiences of medical graduates navigating Georgia's residency enrollment process, as well as residents’ postgraduate training experiences, to identify key areas for improvement. Additionally, we examined attitudes towards enrolling in residency programs abroad to better understand the potential impact on the ongoing phenomenon of “brain drain.” Methods This study employed a qualitative research design based on individual interviews, conducted via Zoom. We explored the experiences and perceptions of residency enrollment among a purposefully selected sample of 10 participants using reflexive thematic analysis. Results We identified six overarching themes. Participants described the placement exam as being of suboptimal quality and reported challenges in navigating the enrollment process, often accompanied by emotional stress. Working in residency without a salary was considered unfair and posed an economic burden. The absence of structured mentorship further contributed to dissatisfaction, prompting several participants to consider alternative career paths or pursue residency opportunities abroad. Conclusion Georgia's medical residency enrollment process requires greater transparency and reduced burdens on aspiring professionals to attract the most qualified candidates. Policy reforms and strategic initiatives should promote socioeconomically equitable access to residency programs and address concerns related to “brain drain,” ultimately supporting the development of a sustainable healthcare workforce.